Ecofeminismo e Modernidade: Uma Análise da espiritualidade ecológica do grupo ConSpirando em Santiago do Chile - Alves, Ana Carolina Chizzolini (2006)
Our research has its objective to analyse the connexion between ecofeminist spirituality and New Age culture. These connexion are perceivel through the movement of individuals who look for health, religious simbols and esoterism in the urban scenery. This phenomenon is called the New Age culture. But the research does not treat of the theme New Age only. It is necessary to make a choice for an individuals group that has the profile of these emerging spiritualities in order that we have a vision of the New Age phenomenon. And it is only possible to happen if we construct an analyse between New Age and other apparent spiritual expression. To make this dialogue, we bring as example a modern an emerging spirituality, i. e., the Ecofeminism. The Ecofeminism is a product of the modernity and they have structures either in their developmant or visualization in the New Age. We understand that to analyze the knitted relation between Ecofeminism and New Age is a way to understand, the indicators of the emerging spiritualities. We take for granted that these spiritualities are kaleidoscopics, fluids and they indicate the individuals as actors of religious choices.